Local Skill Development from China's Engagement in Africa: Comparative Evidence from the Construction Sector in Ghana - Qingwei Meng; Eugene Bempong Nyantakyi (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2019)
Over the past decade, Chinese enterprises have made significant progress in developing new business ventures in Africa, yet there is ongoing debate about whether these Chinese enterprises contribute to local skill development of their host countries. To inform this debate, Qingwei Meng and Eugene Bempong Nyantakyi use survey data from the construction sector in Ghana to examine the heterogeneity in skill transfer to local workers in Chinese enterprises, other foreign and local enterprises, and the challenges faced by firms in local skill development. The results show that both Chinese and other foreign owned enterprises contribute positively to local skill development through the provision of general and specific training. However, Chinese enterprises have a higher propensity to provide short-term general training to local workers than those of other foreign enterprises.
Keywords: 330